Simulation model to assess the validity of the clinical portfolio diet score used in the PortfolioDiet.app for dietary self-tracking: a secondary analysis of a randomized controlled trial in hyperlipidemic adults - Kavanagh, Meaghan E.; Glenn, Andrea J.; Chiavaroli, Laura; Morgan, Gloria A.; Josse, Robert G.; Malik, Vasanti S.; Marinangeli, Christopher P. F.; Kendall, Cyril W. C.; Jenkins, David J. A.; Sievenpiper, John L. (Frontiers in Nutrition, 2024)
The Portfolio Diet combines cholesterol-lowering plant foods for the management of cardiovascular disease risk. However, the translation of this dietary approach into clinical practice necessitates a user-friendly method for patients to autonomously monitor their adherence. Objective: This study aimed to develop and validate the clinical-Portfolio Diet Score (c-PDS) as a food-based metric to facilitate self-tracking of the Portfolio Diet. Methods: Using a simulation model to estimate the c-PDS, the validity was assessed in a secondary analysis of a completed trial of the Portfolio Diet in 98 participants with hyperlipidemia over 6 months. Concurrent and predictive validity of the estimated c-PDS were assessed against the reference measure (weighed 7-day diet records) and concomitant changes in LDL-C from baseline to six months. Bland-Altman analysis was used to assess the limits of agreement between the two methods. Results: The c-PDS was positively correlated with dietary adherence as measured using the 7-day diet records (r=0.94, P<0.001). The c-PDS was negatively correlated with change in LDL-C (r=-0.43, P<0.001) with a 1-point increase in the c-PDS being associated with a -0.04 mmol/L (CI:-0.06,-0.03; P<0.001) or a 1.09% reduction in LDL-C. Visual evaluation of the Bland-Altman plots showed reasonable agreement.These findings indicate good validity of the c-PDS for primary prevention adults with hyperlipidemia and have informed the messaging and goals within the PortfolioDiet.app, a clinical health application for delivering the Portfolio Diet. Future research will assess if the c-PDS when used as part of the PortfolioDiet.app is effective in promoting behaviour change and subsequent health-related outcomes.